Electrical properties of 3-component piezoelectric thick films by screen printing method - Kim, YB; Kim, HJ; Cheon, CI; Choi, DJ; Kim, TS (TAYLOR & FRANCIS LTD, 2001)
PZT(52/48) thick films with Pb-based complex oxide (PCW) additive were prepared on Pt/TiO2/YSZ/SiO2/Si substrate by screen printing method. PCW addition and PZT sol application are performed to fabricate high density PZT thick film and to lower sintering temperature. With the increase of sintering temperature, electrical properties of screen-printed films were improved. Further, for the sol-gel treated thick films, the electrical properties were improved as compared to only screen-printed films. For the PZT-0.12PCW thick films with sol-treated and sintered at 900degreesC, the remanent polarization (P-r) was about 23.8 muC/cm(2) at the applied filed of 150 kV/cm(2), the dielectric permittivity (epsilon(r)) was 1024 at the frequency of 100 kHz, and the piezoelectric coefficient (d(33)) was 339 pC/N at the applied pressure of 1 atm. Finally, the application of these PZT thick films to piezoelectric actuator is described.
Keywords: SILICON